The Marriage of Note and Word in Two Songs by the Gershwins - Allen Forte (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
The author investigates various ways in which George Gershwin’s music and Ira Gershwin’s lyrics are ingeniously interconnected in two songs: “How Long Has This Been Going On?” (1927) and “Who Cares” (1931). The music’s melodies, motives, harmonies, and forms are tied to the lyrics’ rhymes, alliterations, and semantic meanings. The author demonstrates that the designs found in the songs are multi-directional: notes refer to other notes and words, and words refer to other words and notes; the relations are symmetrical. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part III).